태국 간호대학생의 감성지능과 자기효능감이 임상실습스트레스에 미치는 영향 - PIMNON THANYAKORN (The Graduate School, Ajou University, 2024)
본 연구는 태국 간호대학생의 감성지능, 자기효능감과 임상실습스트레스의 정도를 파악하고 임상실습스트레스에 영향을 미치는 요인을 확인하기 위한 횡단적 조사연구이다. 연구 대상자는 태국 소재한 일개 대학교에 재학 중인 3학년과 4학년 간호대학생 156명으로 2023년 10월 9일부터 2023년 10월 16일까지 온라인 설문지를 이용하여 자료 수집하였다. 감성지능은 태국 보건부, 정신건강학과(2000)가 태국 일반 성일을 대상으로 개발한 감성지능 척도(ThaiEmotional Intelligence Screening Test, TEIST)를 사용하여 측정하였으며 자기효능감은 Schwarzer와 Jerusalem(1997)의 일반적 자기효능감 척도(The General Self-Efficacy Scale)를 Sukmak, Sirisoonthon과 Meena (2002)이 태국어로 번안한 자기효능감 측정도구를 이용하여 측정하였다. 임상실습스트레스는 Pagana (1989)의 임상실습스트레스 척도(Psychometric evaluation of the Clinical Stress Questionnaire, CSQ)를 이용하여 측정하였다. 자료분석은 IBM SPSS version 25.0 프로그램을 이용하여 기술통계, independent t-test, one-way ANOVA, Pearson's correlation coefficients, Multiple linear regression으로 분석하였다. _x000D_ _x000D_ 본 연구의 결과를 요약하면 다음과 같다. _x000D_ _x000D_ 1. 본 연구결과 대상자의 감성지능은 총 208점 만점 중 평균 158.11점, 자기효능감은 총 40점 만점 중 평균 26.23점, 임상실습스트레스는 총 100점 만점 중 42.49점으로 나타났다._x000D_ 2. 대상자의 일반적 특성에 따른 임상실습스트레스의 차이를 확인한 결과는 전공만족도(F=14.121, p<.001) 및 임상실습만족도(F=7.344, p=.001)에 따라 임상실습스트레스에 통계적으로 유의한 차이를 나타냈다._x000D_ 3. 대상자의 감성지능, 자기효능감과 임상실습스트레스 간의 관계를 분석한 결과 임상실습스트레스는 감성지능_x000D_ (r=-.60, p<.001), 자기효능감(r=-.51, p<.001)과의 통계적으로 유의한 음의 상관관계가 있는 것으로 나타_x000D_ 났다._x000D_ 4. 대상자의 임상실습스트레스의 영향을 미치는 요인을 확인하기 위해 다중회귀분석을 실시한 결과 전공만족도가 보통인 군(β=0.16, p=.033), 전공만족도가 불만인 군(β=0.23, p=.004), 감성지능(β=-0.41, p<.001), 자기효능감(β=-0.19, p=.028)이 임상실습스트레스에 통계적으로 유의한 영향을 미치는 것으로 나타났으며 설명력은 43%이었다. _x000D_ _x000D_ 이상의 결과를 통하여 태국 간호대학생의 감성지능 및 자기효능감을 확인하고, 임상실습스트레스에 대한 관계를 규명하고 임상실습스트레스에 영향을 미치는 변수를 확인하였다. 따라서 이를 바탕으로 임상실습스트레스를 완화시키기 위해서는 내적요인인 감성지능을 높이는 교육과 중재 프로그램을 개발하고 자기효능감을 개선시키고 전_x000D_ 공만족도를 향상시킬 수 있는 교육 프로그램을 통해 태국 간호대학생의 임상실습스트레스를 감소될 것으로 기대_x000D_ 한다.|This study was a cross-sectional correlational study to examine the emotional intelligence, _x000D_ self-efficacy and clinical practice stress of Thai nursing students and to identify the factors in_x000D_ fluencing clinical practice stress. The study population was consisting of 156 Thai nursing students who is attending third year and fourth year class in a university located in P district in _x000D_ Thailand.The study was conducted from October 9, 2023 to October 16, 2023 and data were collected by using online Google forms. The Thai Emotional Intelligence Screening Test, TEIST which developed by the Department of Mental Health, Ministry of Health, Thailand (2000) was used to measure the level of emotional intelligence. The General Self-Efficacy Scale which developed by Schwarzer and Jerusalem (1997) and translated to Thai by Sukmak, Sirisoonthon _x000D_ and Meena (2002) was used to measure the level of self-efficacy. Psychometric evaluation of the Clinical Stress Questionnaire, CSQ which developed by Pagana (1989) was used to measure the level of clinical practice stress. Data was analyzed using IBM SPSS 25.0 program and using descriptive statistics, independent t-test, one-way ANOVA, Pearson's correlation coefficient, and multiple linear regression. _x000D_ _x000D_ The main results of the study are as follows._x000D_ _x000D_ 1. The students' emotional intelligence averaged 156.11 points out of 208 points the mean scores of self-efficacy were 26.23 points out of 40 points, and clinical practice stress were 42.49 points out of 100 points._x000D_ 2. As a result of analyzing the differences in clinical practice stress level according to general characteristics, there was a statistically significant difference in clinical practice stress among Thai nursing students based on major satisfaction (F=14.121, p<001), and a statistically significant difference in clinical practice stress among Thai nursing students based on clinical prac_x000D_ tice satisfaction (F=7.334, p=.001)._x000D_ 3. There was a statistically significant negative correlation between clinical practice stress and emotional intelligence (r=-.60, p<.001). Additionally, there was a statistically significant negative correlation between clinical practice stress and self-efficacy (r=-.51, p<.001)._x000D_ 4. Multiple regression analysis was conducted to identify factors affecting clinical practice stress among Thai nursing students. The results showed that the group with average satisfact_x000D_ ion with major (β=0.16, p=.033), group with dissatisfaction with major (β=0.23, p=.004), emotional intelligence (β=-0.41,p<.001), self-efficacy (β=-0.19, p=.028) had statistically significant effects on clinical practice stress, with an explanatory power of 43%._x000D_ _x000D_ Through the above findings, it has been confirmed that the emotional intelligence, self-efficacy and major satisfaction of Thai nursing students were important influencing factor for clinical practice stress. Therefore, results of the study can be used as a basis for enhance emotional intelligence, self-efficacy, and major satisfaction among Thai nursing students through education program development to reduce clinical practice stress of Thai nursing students in the _x000D_ future.
학위논문(석사)--간호학과,2024. 2
Keywords: 감성지능; 임상실습스트레스; 자기효능감; 태국 간호대학생